Online Gender-Based Violence in Marriage as Grounds for Fasakh: A Normative Study of Islamic Family Law and Law No. 12 of 2022 - Mohammad Azka Hakim; Azmil Mukarrom (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This article examines the position of Online Gender-Based Violence (KBGO) in marriage as a ground for fasakh (judicial dissolution of marriage) under Islamic family law and Indonesian positive law. Data from the National Commission on Violence Against Women (CATAHU 2024) indicates a significant rise in KBGO cases; however, the Compilation of Islamic Law (KHI) does not explicitly recognize KBGO as a basis for divorce. This study employs a normative legal research method with statutory and conceptual approaches. Primary legal sources include the Quran, Hadith, KHI, and Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS), supplemented by classical fiqh literature across the four Sunni schools. The findings indicate: first, KBGO perpetrated by a husband constitutes a severe form of dharar that systematically destroys three pillars of maqashid syariah hifdz al-nafs, hifdz al-'irdh, and hifdz al-aql; second, KBGO can be legally constructed as a valid ground for fasakh through progressive interpretation of Article 116(d) and (g) of KHI in conjunction with Articles 13–17 of UU TPKS. The study concludes that synchronizing KHI with UU TPKS provides a solid legal foundation for Religious Court judges to grant fasakh based on digital violence under the maxim la dharara wa la dhirara. An amendment to KHI or a Supreme Court Regulation (PERMA) explicitly accommodating KBGO as grounds for marriage dissolution is urgently recommended.